8 ASN-IRSN Survey on in vivo dosimetry in external radiotherapy: what solutions and strategies to push the frontier of "technically measurable"?. (December 2018) - Roch, P.; Isambert, A.; Etard, C.
Abstract : Introduction: In Vivo Dosimetry (IVD) is mandatory in France for every "technically measurable" beam, since 2008 (criterion No. 15 of National Cancer Institute, for the practice of external radiotherapy). IVD was historically based on punctual measurement techniques adapted to conventional radiotherapy. The applicability of this method has greatly decreased with the dissemination of modulated radiotherapy techniques (IMRT, VMAT). The majority of French radiotherapy centers practice these advanced techniques (nearly 70% of them in 2013[1] ), for sometimes 100% of the treatments. So, the proportion of "non-technically measurable" beams grows very rapidly and new solutions must be considered to ensure a satisfactory level of treatments control. From this statement, resulting from the practices observed during inspections, Nuclear Safety Authority (ASN) wished to know what IVD solutions - especially those called "transit" based on the use of the portal imaging device (EPID) – are available or in development, the technical and organizational constraints of the "transit" IVD and its relations with other types of controls. Methods: IRSN met providers of IVD solutions, or comparable control systems, and visited radiotherapy departments experienced in the field of transit IVD. The Medical Physicists representatives (SFPM) point of view has been collected, in continuation with the SFPM work of 2014[2] . Results: This study focused on main "transit" IVD solutions currently proposed and nearly expected, as well as alternative or complementary solutions such as the analysis and monitoring of the LINAC parameters. Interviews with medical physicists revealed that IVD is part of an overall process of dose verification and cannot replace the controls performed without the patient. The definition of the intervention criteria or validation of DIV results, the identification of dose gap origin of and the interpretation of the results are the main mentioned difficulties, as well as the ergonomics of the devices, the tools of monitoring and analysis, the accessibility of data and the need for consistent human resources. The teams' expectations with respect to IVD, and therefore the requirements and resources allocated, can be on one hand a simple wish of regulatory compliance or, on the other hand, to use IVD as an adaptive radiotherapy tool . . Conclusions: The offer of IVD solutions in recent radiotherapy techniques is progressing. The EPID-based IVD is the most widely used but, routinely, is often confined to conventional techniques. The exploitation and interpretability of the results is the main difficulty encountered by the teams, leading them to develop a treatment verification strategy in which the IVD is a one part of dose control and not the ultimate and global solution.